Multiwavelength ytterbium-doped fiber ring laser - Moghaddam, M.R.A.; Harun, Sulaiman Wadi; Paul, Mukul Chandra; Pal, Mrinmay; Dhar, Anirban; Sen, Ranjan; Das, Sumita; Bhadra, Shyamal Kumar; Ahmad, Harith (John Wiley & Sons, 2009)
A multiwavelength Ytterbium-doped fiber ring laser operating at 1030 nm region is demonstrated using a Sagnac loop mirror. The Ytterbium-doped fiber used is drawn from Yb2O3-doped perform, which is fabricated through deposition process in conjunction with a solution doping technique. The loop mirror is constructed using a 3dB coupler and a piece of polarization maintaining fiber (PMF). The fiber laser generates a multiwavelength oscillation with up to five lines by adjusting both polarization controllers in the ring cavity. The line spacing is obtained at 2.1 nm, which is strongly dependent on the PMF's length used.